Face-to-face versus distance learning: perception of the academic community at ESTeSL - Poças, Ilda Maria (2022)
Introduction: Facing the pandemic situation of COVID 19, which reached Portugal in 2020, higher education institutions needed to adapt, transitioning from face-to-face learning to distance emergency learning, and therefore, in an online format. Objectives: To analyze the academic community's perception of a higher school of health facing the learning transition, focusing mainly on the preference and satisfaction for the type of learning, adaptation difficulties, motivation, changes in emotional states, academic performance, acquired skills, and visual changes.